Research into the Mechanical Properties of Drawn Filament Sewing Thread (Journal of Fiber Bioengineering and Informatics, 2012)
This study presents research into drawing conditions' influences on the mechanical properties ofPolyethylene Terephthalate (PET) filament sewing thread. The thread was drawn by varying thetreatment temperature and contact time on the first heated cylinder (T1, n1) and on the second heatedcylinder (T2, n2), as well as by using different draw ratios (λ). The critical treatment conditions werefound using the drawing process (T1_4=130 °C, n1_5=13 turns, λ_5=1.25, T2_4=220 °C, n2_3=9 turns)and the greatest improvement in the mechanical properties, respectively. Deterioration in the threads'mechanical properties was observed above the critical treatment conditions. The mechanical propertiesof the drawn threads were investigated under critical treatment conditions. It was found that the heattreatment conditions on the second cylinder, i.e. the treatment temperature and the contact time had thegreatest influences on the improvement of the elastic modulus (D4=7.41 cN/tex, E3=7.40 cN/tex) andthe breaking extension (D4=12.13%, E3=12.12%), when compared with the treatment temperature andthe contact time on the first cylinder and the draw ratio between the heated cylinders. The maximal valueof the breaking tenacity showed threads that were drawn at the critical draw ratio (C5=61.81 cN/tex)and the contact time of the thread with the second heated cylinder (E3=61.59 cN/tex). Simultaneously,the treatment conditions on the second cylinder affected the maximum reduction of the thread's lineardensity (D4=91.33 tex, E3=91.47 tex) and twist (D4=163 turns/m, E3=180 turns/m). The greatestimprovement in the tension at the yield point achieved threads that were drawn at the critical drawratio (C5=9.27 cN/tex) and the heat-treatment temperature on the second cylinder (D4=9.27 cN/tex).